Research on the flow of international students to the United Kingdom universities: determinants and implications - Naidoo, Vik (Sage Publications, 2007)
Using time series data over the 1985–2003 period, this article examines some of the determinants of international student mobility to universities in the UK. The research found that some of the main factors influencing international student mobility to the UK include access to domestic education opportunities in the source country, the level of tuition fees in the host country and the level of involvement of the source country in the global economy. At a time when recruiting international students is getting more competitive, these findings will provide the international student recruiter with an enhanced understanding of the dynamics of the international education sector.